Hope Surfacing: An Investigation Into Documentary Modes for Telling the Stories of Families who Support a Family Member who has Experienced Mental Distress - Lavranos, Eileen (Auckland University of Technology, 2015)
This work is a creative production PhD project that consists of a documentary artefact and an exegesis. The documentary project entailed investigating ways to create a process of working ethically with sensitive material and in doing so has integrated two significant inquiries. The first relates to the designing of protocols for working ethically with sensitive material and vulnerable people. The second is the design of a documentary called Hope, that captures the stories of six families who are supporting a family member with a mental illness. This situation can leave such families isolated, under stress and often experiencing stigma and discrimination. Because very little training is available to families in these circumstances, the documentary captures personal narratives so that certain issues in common can be identified. This is achieved while simultaneously acknowledging the unique and authentic nature of individual family experience. The result is that these stories contain information about caregiving that is seldom discussed and in so doing the documentary provides observations that can be of assistance to others. [Documentary artefact permanently embargoed]
Keywords: Documentary; Narrative; Ethics; Family caregivers; Mental illness; Practice